The Effects of Multipath on the Performance of High Rate Digital QAM and OFDM Wireless Link Operating in Tunnels - Yehuda Taragin; Niv Elkayam; Gad A. Pinhasi; Yosef Pinhasi (IEEE Access)
Wide-band wireless communication in tunnels and long corridors faces challenges due to multipath interferences and delay spread. Wall reflections induce dispersion, causing amplitude and phase distortions in the received signal, with the extent of distortion determined by multiple factors. Accurate modeling of space-frequency effects is essential for designing reliable indoor wireless links. This study presents an experimentally validated, precise, and versatile model for the propagation of modulated wireless signals in tunnels. Quasi-optical, multi-ray model is employed to derive the transfer function, describing the indoor propagation in the frequency domain. The model enables analysis of the impact of changes among other in modulations, frequencies, and different bandwidths. The results include a comprehensive comparison of various cases for Bit Error Rate (BER), Error Vector Magnitude (EVM), constellations, and facilitating a thorough examination of the tunnel effects in each scenario. Several representative results are presented in the paper. Notably, a significant correlation is observed between the bandwidth used and an increase in BER. Furthermore, the comparison between Orthogonal Frequency Division Multiplexing (OFDM) and Quadrature Amplitude Modulation (QAM) reveals a distinct preference for OFDM due to its ability to overcome the frequency-selective fading nature of the tunnel.